1992
DOI: 10.1016/0014-5793(92)80693-b
|View full text |Cite
|
Sign up to set email alerts
|

Validity of putative calcium binding loops of photoprotein aequorin

Abstract: Three peptides containing the putative Ca2+ binding loops, I, II and III, respectively, of a photoprotein, aequorin, from jellyfish Aequorea victoria were synthesized by a solid‐phase procedure. The peptides bound Ca2+ with dissociation constants or 10−3 to 10−4 M, providing evidence for the assumption that Ca2+ binding loops are actually responsible for the binding of Ca2+. When the highly conserved 6th glycine residue in the 12‐residue loops was replaced by arginine, no large effect was observed on Ca2+ bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…In contrast, for aequorin it is suggested that the Ca 2+ ‐binding loop III located in the C ‐terminal domain has the highest affinity to Ca 2+ as compared to the affinities of other Ca 2+ ‐binding loops. This conclusion is based on the determination of K D for Ca 2+ of synthetic peptide fragments of 20–22 amino acid residues that mimic the aequorin EF‐hand motifs 39 as well as NMR studies on binding of magnesium ions with Ca 2+ ‐binding loops of aequorin 40 . If this is the case then Ca 2+ ‐binding sites with the highest affinity to Ca 2+ can have different location in different Ca 2+ ‐regulated photoproteins.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, for aequorin it is suggested that the Ca 2+ ‐binding loop III located in the C ‐terminal domain has the highest affinity to Ca 2+ as compared to the affinities of other Ca 2+ ‐binding loops. This conclusion is based on the determination of K D for Ca 2+ of synthetic peptide fragments of 20–22 amino acid residues that mimic the aequorin EF‐hand motifs 39 as well as NMR studies on binding of magnesium ions with Ca 2+ ‐binding loops of aequorin 40 . If this is the case then Ca 2+ ‐binding sites with the highest affinity to Ca 2+ can have different location in different Ca 2+ ‐regulated photoproteins.…”
Section: Resultsmentioning
confidence: 99%
“…Le système aequorine isolé de la méduse Aequora Vic toria, est composé de l'apoaequorine, peptide de 189 acides aminés, et d'un chromogène, la coelentérazine (Charbonneau et al, 1985). La fixation du calcium au niveau des sites de fixation spécifiques (Oishi et al, 1992) entraîne un changement conformationnel provo quant l'oxydation du chromogène en coelentéramide avec émission d'une onde lumineuse de 470 nm. Le sys tème peut être étalonné afin que l'intensité de la lumière émise soit directement proportionnelle à la quantité de calcium libre dans le milieu (Watkins et al, 1995).…”
Section: Le Système Chimioluminescent Aequorine Clonage Et Expression...unclassified